Psychological and social problems of creating a culture of life the people with disability - Liovochkina, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
This article is analysis of the problems of forming ecological way of life of persons with disability. The factors that are effective in the way of life of people with limited functionality that make up the so-called "complex invalid". It is shown that "disability syndrome" ("complex invalid") are includes: rent expectations; position "victims"; feeling lost health; symptom exceptionalism; "losing of sense of future"; symptoms of learned helplessness; a filling of lost opportunities and a feeling of lost happiness. We have identified ways and principles of psychological and social work with the disabled and proposed concept of a habilitation and rehabilitation programs for persons with disabilities, carried out for the purpose of socialization or re- socialization. These are the principles: the ecological principle, the principle of unity of consciousness and activity and the principle of empowerment. In particular, if we follow the principle of environmental friendliness, it is necessary to organize human activities to it due to elements of the environment, create environment for its development. The concept of creating a program of rehabilitation and habilitation of persons with disability was carried out for the purpose of socialization or re-socialization. We set up a table to help build step by step program of rehabilitation of people with disabilities. Psychologist or social worker should be created the program of rehabilitation together with the subject of development.